Design research on a smart infusion device to reduce medical workload and enhance patient safety - Bo Mu; Yilun Wang; Xunchen Liu; Mohammad Puad Bebit; Mingzhang Chen; Hailin Wu; Wei Zhang; Lanxin Wang; Yuan Fang; Kang Dong (Scientific Reports)
Abstract In traditional infusion processes, issues such as untimely medication replacement and patients’ difficulty in continuously monitoring their medication levels are prevalent. This study presents the design of a smart infusion automatic medication replacement device aimed at automating infusion management through three key modules: high-precision liquid level monitoring, automated medication replacement, and a smart control system. By monitoring liquid levels in real time, the system eliminates the need for patients to constantly check their medication levels, accurately controlling the amount of medication dispensed and transmitting monitoring signals within safe thresholds. The rotational medication replacement mechanism stores and precisely replaces medicine bottles, optimizing usage and minimizing waste. Automated settings for liquid level monitoring and the plug-and-push system replace the need for manual assessment of medication completion and input quality, ensuring consistent dosage and high-quality delivery. The rotational mechanism also reduces the time needed for refilling and decreases the labor intensity for healthcare providers. A stabilization and calibration mechanism ensures bottles remain centered, preventing issues with internal pressure changes and loosening of the piercing tool. By replacing repetitive manual adjustments with automated processes, healthcare professionals can focus more on patient care rather than the cumbersome medication replacement procedures. The smart infusion automatic medication replacement device enhances the quality of infusion therapy for patients and alleviates the repetitive workload of medical staff.